2016
DOI: 10.1136/bmjdrc-2016-000250
|View full text |Cite
|
Sign up to set email alerts
|

Lost opportunities to prevent early onset type 2 diabetes mellitus after a pregnancy complicated by gestational diabetes

Abstract: ObjectivesGestational diabetes mellitus (GDM) greatly increases the risk of developing diabetes in the decade after delivery, but few women receive appropriately timed postpartum glucose testing (PPGT) or a referral to primary care (PC) for continued monitoring. This qualitative study was designed to identify barriers and facilitators to testing and referral from patient and providers' perspectives.MethodsWe interviewed patients and clinicians in depth about knowledge, values, priorities, challenges, and recom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
70
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(73 citation statements)
references
References 42 publications
3
70
0
Order By: Relevance
“…Neufeld has similarly documented how women with GDM perceive their treatment as strict and controlling, and have challenges with food cravings . The finding that women with GDM exhibit a high degree of motivation to change their lifestyle based on concerns for their baby has likewise been reported in other studies . As evidence suggests that a mother's lifestyle influences her offspring during childhood , the question thus becomes how to channel and sustain this motivation to ensure the health of both the mother and the child in the years following a GDM pregnancy.…”
Section: Discussionmentioning
confidence: 78%
“…Neufeld has similarly documented how women with GDM perceive their treatment as strict and controlling, and have challenges with food cravings . The finding that women with GDM exhibit a high degree of motivation to change their lifestyle based on concerns for their baby has likewise been reported in other studies . As evidence suggests that a mother's lifestyle influences her offspring during childhood , the question thus becomes how to channel and sustain this motivation to ensure the health of both the mother and the child in the years following a GDM pregnancy.…”
Section: Discussionmentioning
confidence: 78%
“…Some respondents indicated that they did not understand how the test worked, meaning one participant ate breakfast so had to come back another time , and another questioned the procedure saying, ‘… How can you give somebody sugar to drink and then you're going to have to test it? They're definitely going to find the sugar’ . Several suggested using more pleasant tests .…”
Section: Resultsmentioning
confidence: 99%
“…Finally, the need to work presented a further barrier to attendance because women were not able to take time away for the test: ‘I couldn't leave work because they could take it away and I knew the situation I was in, I needed to work’ , and it presented another demand on their time: ‘… I've been running around trying to get stuff done before I go back to work’ (screened) .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have identified several risk factors associated with the onset of T2DM such as physical inactivity, alcohol and tobacco consumption, diet, family history of diabetes, aging, obesity, prior history of gestational diabetes, impaired glucose tolerance, race/ethnicity, (6)(7)(8)(9)(10)(11)(56)(57)(58), high blood pressure (12), appendicectomy (13), hypothyroidism (14), depression and anxiety (59). Pharmacological factors such as the use of statins also increases the risk of T2DM by 10-12% (60), statins have a dose dependent class effect on new-onset T2DM, i.e., the risk of developing T2DM increases with the increase in statin dose (61).…”
Section: Risk Factors -Onsetmentioning
confidence: 99%